Development of Video Media in ICT Learning for Middle Year Students in Junior High Schools - Zulfi, Difa Adani; Bentri, Alwen; Eldarni, Eldarni; Kurnia Yusri, Meldi Ade (Jurnal Aplikasi IPTEK Indonesia, 2024)
One challenge encountered in the learning process is the inadequate utilization of digital-based learning media during study sessions. Thus far, traditional learning materials have been employed, including textbooks and workbooks. The research problem at hand pertains to the insufficient utilization of digital-based media for ICT Guidance instruction in junior high school classes VIII. This study intends to generate high-quality instructional videos. Using the 4-D development model, this form of research is development research known as Research & Development (R&D). The phases of this development model are as follows: define, design, develop, and disseminate. Three validators, including two media expert validators and one material expert validator, conducted the media validator test. A practicality exam was administered to 32 eighth-grade students from Padang City State Middle School 22 in order to evaluate the efficacy of the instructional video product. Based on the findings of the study, material validation results average 4.8 and are classified as "Very Valid," media validator 1 validation results average 4.9 and are categorized as "Very Valid," and media validator 2 validation results average 4.7 and are categorized as "Very Valid." The results of product practicality trials, which average 4.4, are classified as "Very Practical." Hence, this medium is appropriate for utilization.